Dynamic behaviour of an inclined FG-CNTRC sandwich beam under a moving mass - Tran, Thi Thom; Esen, Ismail; Nguyen, Dinh Kien (Vietnam Journal of Science and Technology, 2024)
This paper studies dynamic behavior of an inclined sandwich beam with a homogeneous core and functionally graded carbon nanotube reinforced composite (FG-CNTRC) face sheets under a moving mass. The effective properties of the face sheets are estimated by the extended rule of mixture. Three types of carbon nanotube distribution, namely uniform distribution (UD), functionally graded ( ) and V (FG-V) distributions, are considered. Based on the first-order shear deformation theory, a finite element formulation is formulated by using hierarchical functions to interpolate the displacements and rotation. Using the derived formulation, dynamic response the sandwich beam is computed with the aid of the Newmark method. The obtained result reveals that the inclined angle has a significant influence on the response of the beam, and the dynamic magnification factor decreases for the beam associated with a larger inclined angle. The effects of various parameter, including the nanotube volume fraction, the type of carbon nanotube distribution, the layer thickness ratio and the moving mass velocity on dynamic behavior of the sandwich beam are examined and highlighted.